Clinical Case of Unprotected Left Main Percutaneous Coronary Intervention in Elderly Patient With Porcelain Aorta - Sergii V. Salo; Andrii Yu. Gavrylyshyn; Olena V. Levchyshyna; Vitalii V. Tokhtarov; Artem Yu. Hladun (Ukrainian Journal of Cardiovascular Surgery, 2022)
Coronary artery bypass grafting (CABG) has long been considered the gold standard in the treatment of patients with lesions of the left main (LM) coronary artery. Elderly patients are one of the most difficult categories of patients with LM lesions due to severe coronary artery calcification. Thanks to constant progress in the field of engineering and technology, it has become possible to perform percutaneous coronary interventions (PCI) for patients with unprotected stenosis of the LM. Drug-eluting stents and the development of pharmacotherapy have improved the results of PCI in these lesions. Comparative studies of the efficacy and safety of PCI and CABG have shown similar results in terms of the need for revascularization. Patients with severe calcification of the coronary arteries mostly belong to the older age group and hold large part in this cohort. Technological advances enabled to treat patients with complex coronary anatomy and LM lesions not only through CABG, but also through PCI. Comparative studies show that the efficacy and safety of PCI and CABG have similar results in terms of the need in revascularization.The aim. To highlight the importance of discussion of each clinical case by the heart team and comprehensive approach with the use of modern equipment.Stage 1. A 80-year-old woman with type 2 diabetes mellitus was delivered by an ambulance team to the National Amosov Institute of Cardiovascular Surgery with severe pain; the patient was diagnosed with non-ST-elevation myocardial infarction (NSTEMI). Electrocardiography revealed ST-segment depression in leads V1-V5. After performing echocardiographic examination, valvular pathology and segmental contraction defects were not detected, EF 52%.Urgent coronary angiography revealed significant calcification of the ascending aorta (porcelain aorta) and coronary arteries. Coronary artery lesions: 90% unstable LM stenosis, significant calcified stenosis of the circumflex artery (CA), middle left anterior descending artery (mid-LAD), and chronic coronary occlusion of the right coronary artery, besides, 5 episodes of ventricular tachycardia were recorded. Despite the high SYNTAX Score I and SYNTAX Score II, due to the clinical picture and heart rhythm disorders, the heart team decided to perform emergency PCI. Bare-metal stent for LM – mid-LAD was implanted and angioplasty of mid-LAD was performed. Rough calcification of LM caused stent recoil; postdilatation of LM stent by high pressure balloon (p = 25 atm) was performed. The operation ended with a good angiographic result. The woman was discharged in a stable condition to plan further intervention in 1 month.Stage 2. A 81-year-old woman with complaints of severe chest pain was re-hospitalized with NSTEMI to the National Amosov Institute of Cardiovascular Surgery 3 months after the primary PCI. Echocardiography revealed EF 53%; valvular pathology and segmental contraction defects were not detected. Urgent coronary angiography revealed 90% of LM stenosis (stent recoil – loss of radial rigidity). Gradual angioplasty of LM stenosis and CA stenosis were performed.Stage 3. For reinforcing the radial rigidity in LM, LM – CA drug-eluting stent was implanted. Angioplasty of LM and CA using kissing balloon technique was performed. Final proximal optimization of LM showed good angiographic result.